2004
DOI: 10.1520/jfs2003276
|View full text |Cite
|
Sign up to set email alerts
|

Death by Chainsaw: Fatal Kickback Injuries to the Neck

Abstract: Each year over 3 million new chainsaws are sold in the United States. The operation of these newer saws combined with the millions of older chainsaws in circulation results in over 28,000 chainsaw-related injures annually. The majority of the injuries involve the hands and lower extremities with less than 10% involving injuries to the head and neck regions. Deaths while operating a chainsaw are extremely rare. The most common hazards associated with chainsaws are injuries caused by kickback, pushback, and pull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 4 publications
2
25
0
Order By: Relevance
“…3,4 However, in the forensic literature described here are rare circular saw and chainsaw suicidal attempts in patients with schizophrenia or depression and in homicides as well. 5Y8 The usual scenario of chainsaw, circular saw, and grinding saw injuries of the head and neck includes injury of soft tissues.…”
mentioning
confidence: 83%
“…3,4 However, in the forensic literature described here are rare circular saw and chainsaw suicidal attempts in patients with schizophrenia or depression and in homicides as well. 5Y8 The usual scenario of chainsaw, circular saw, and grinding saw injuries of the head and neck includes injury of soft tissues.…”
mentioning
confidence: 83%
“…In the medico-legal literature, the use of electrical saws/chain saws is mainly associated with accidents [1,2]: most injuries are caused by saw kickbacks and concern the left side; the face, neck, hands and feet are mainly involved. In addition, intentional selfmutilations, insurance fraud or postmortem body dismemberment were described [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…3,9 The main cut is generally straight but may present some tags in the side walls which are extensively contused. 3,9,11 Wound morphology is determined by the shape of the saw teeth whose perpendicular cutting surfaces are designed to cut and remove wood (see Fig. 1).…”
Section: Neck Injuries In Chainsaw Suicidesmentioning
confidence: 99%
“…1 As a result, the wounded tissue is cut, bruised, chewed and coarsely removed while the margins of the wound may often be contaminated with foreign oily substances, sawdust or wood chips, bark, grease, bacteria or fungal microspores normally lodging on the chain and teeth. 9,11 The teeth's chewing effect produces an accumulation of coarser, heavier fragments of tissue below the cutting attachment while smaller, lighter fragments of tissue and blood are normally launched ahead from the tip of the bar. 12 Schiwy-Bochat et al reported that the saw teeth normally slip off the skin on initial contact with surface tissues but, after increasing manual pressure, the saw penetrates the deeper tissues causing lethal wounds to the deep vessels and nerves of the neck as far as the cervical spine bones.…”
Section: Neck Injuries In Chainsaw Suicidesmentioning
confidence: 99%
See 1 more Smart Citation